Identitas Seniman Tari Barong dan Keris terhadap Komodifikasi Tari Sakral di Batubulan - Bagus Merta Dana (Institut Seni Indonesia Denpasar, 2022)
Barong and Keris Dance is a sacred dance that can attract tourists; therefore, it is shown as a cultural tourist attraction. However, this condition raises questions about the central identity of a dancer who contributes to sacred dance performances and tourist attractions. Therefore, this research examined a dancer’s central identity and motivations. This research is qualitative research with a narrative approach. The data collected was from observation, interviews, and a literature study with three findings. Firstly, the dancer has two identities as pengayah and tourism actor, whereas pengayah is his central identity. Secondly, the existence of Barong dan Keris Dance encourages him to devote his dance skill to society and God. Lastly, in this condition, the existence of cultural commodification can support the preservation of a culture.